A New Model of Cuprizone-Mediated Demyelination/Remyelination. (26th September 2014) - Sachs, Hilary H.; Bercury, Kathryn K.; Popescu, Daniela C.; Narayanan, S. Priya; Macklin, Wendy B.
In the central nervous system, demyelinating diseases, such as multiple sclerosis, result in devastating long-term neurologic damage, in part because of the lack of effective remyelination in the adult human brain. One model used to understand the mechanisms regulating remyelination is cuprizone-induced demyelination, which allows investigation of remyelination mechanisms in adult animals following toxin-induced demyelination. Unfortunately, the degree of demyelination in the cuprizone model can vary, which complicates understanding the process of remyelination. Previous work in our laboratory demonstrated that the Akt/mTOR pathway regulates active myelination. When given to young postnatal mice, the mTOR inhibitor, rapamycin, inhibits active myelination. In the current study, the cuprizone model was modified by the addition of rapamycin during cuprizone exposure. When administered together, cuprizone and rapamycin produced more complete demyelination and provided a longer time frame over which to investigate remyelination than treatment with cuprizone alone. The consistency in demyelination will allow a better understanding of the mechanisms initiating remyelination. Furthermore, the slower rate of remyelination provides a longer window of time in which to investigate the diverse contributing factors that regulate remyelination. This new model of cuprizone-induced demyelination could potentially aid in identification of new therapeutic targets to enhance remyelination in demyelinating diseases.